2019
DOI: 10.3389/fmicb.2019.00123
|View full text |Cite
|
Sign up to set email alerts
|

Identification of in vivo Essential Genes of Vibrio vulnificus for Establishment of Wound Infection by Signature-Tagged Mutagenesis

Abstract: Vibrio vulnificus can cause severe necrotic lesions within a short time. Recently, it has been reported that the numbers of wound infection cases in healthy hosts are increasing, for which surgical procedures are essential in many instances to eliminate the pathogen owing to its rapid proliferation. However, the mechanisms by which V. vulnificus can achieve wound infection in healthy hosts have not been elucidated. Here, we advance a systematic understanding of V. vulnificus wound infection through genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 82 publications
0
24
0
Order By: Relevance
“…Bacteria recovered from mice infected with MO6-24/T all had an opaque morphology, indicating that phase switching from translucent back to opaque had likely occurred in vivo by an undetermined mechanism [11]. Attenuation of virulence was a common property seen for acapsular transposon mutants of V. vulnificus in other studies as well [12][13][14].…”
Section: Identification Of the V Vulnificus Capsule And Its Correlatmentioning
confidence: 60%
“…Bacteria recovered from mice infected with MO6-24/T all had an opaque morphology, indicating that phase switching from translucent back to opaque had likely occurred in vivo by an undetermined mechanism [11]. Attenuation of virulence was a common property seen for acapsular transposon mutants of V. vulnificus in other studies as well [12][13][14].…”
Section: Identification Of the V Vulnificus Capsule And Its Correlatmentioning
confidence: 60%
“…Phenotypes in the motility of ΔpomA, ΔcheY, and Q93R, the number of detections from spleen at the two-time points, and the number of dead mice after infection. We previously showed that ΔpomA and ΔcheY were attenuated mutants that could not proliferate enough to be detected from spleen [17]. The detailed study of these mutants here revealed that their ability to invade the muscle and the systemic circulation was reduced (Figures 3(c) and 5(a)).…”
Section: Discussionmentioning
confidence: 72%
“…The Δ pomA and Δ cheY deletion mutants were constructed as described previously [ 17 ]. Briefly, the pomA gene and the cheY gene were amplified and cloned into the suicide vector pYAK1, retaining sacB .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations